A Difunctional Squarylium Indocyanine Dye Distinguishes Dead Cells through Diverse Staining of the Cell Nuclei/Membranes. Issue 7 (16th October 2013) - Li, Jie; Guo, Kunru; Shen, Jie; Yang, Wantai; Yin, Meizhen
<x xml:space="preserve">Abstract</x> Functionalized fluorescent dyes have attracted great interest for the specific staining of subcellular organelles in multicellular organisms. A novel nanometer‐sized water‐soluble multi‐functional squarylium indocyanine dye (D1) that contains four primary amines is synthesized. The dye exhibits good photostability, non‐toxicity and biocompatibility. Isothermal titration calorimetry demonstrates that an affinity between D1 and DNA is higher than that between D1 and analogue of phospholipids. Analysis of circular dichroism spectra indicates that D1 targets to the DNA minor groove and aggregates to a helix. Because of the distinct affinity between the dye and subcellular organelles, the dye exhibits difunctional abilities to label the cell nuclei in fixed cells/tissue and the cell membranes in live cells/tissue. By combination of the two staining capabilities, the dye is further explored as a specific marker to distinguish apoptotic cells in live cells/tissue. The research opens a new way to design novel multifunctional dyes for life science applications.